Isolasi dan Karakterisasi Protease Ekstraseluler dari Bakteri dalam Limbah Cair Tahu - Fatoni, Amin; Zusfahair, Zusfahair; Lestari, Puji (Jurnal Natur Indonesia, 2008)
Protease has been used in large application industrial process such as detergent, leather, textil, softdrink, andmedicine. In order to find unique protease, many substances were explored as proteases of bacteria sources. Inthis study, tofu liquid waste was used as a source of bacteria producing proteases. Waste sample was growth inskim milk agar medium showing proteases activity, it was used to produce extracellular protease. The microbialcolonies were identified as Staphyllococcus sp. Protease was extracted with 5000 g centrifugation at 4 0C, andpurificated with ammonium sulphate precipitation continued with dialisis. Optimum production time, pH, metal ion,EDTA, specific activity, KM, and Vmaks were studied for enzyme characterization. Volume of crude enzyme was 300ml, with spesific activity of 3.55 U/mg. Protease obtained from 60% ammonium sulphate fraction had the highestspecific activity of 68.22 U/mg. Study on the protease characterization revealed that optimum temperature of thisenzyme was 400C. The optimum pH of the enzyme was found to be 8.0. The kinetic parameters K M dan Vmaks withcasein as substrate were 0.31% and 51.55 U/ml. Some inhibitory effect was observed in the presence of EDTA, Cu +2,Co+2, Zn+2, and enzyme activity was stimulated by Mg+2, indicating that this ion had a functional role in the molecularstructure of the enzyme.